Pelatihan Dan Edukasi Pada Guru Paud Tentang Tumbuh Kembang Balita Dan Anak Pra Sekolah - Sunarsih, Tri (Universitas Respati Yogyakarta, 2020)
The need for stimulation or efforts to stimulate children to introduce new knowledge or skills is very important in improving children's intelligence. Stimulation in children can be started since the baby is a fetus, because the fetus is not a passive creature. In the womb, the fetus is able to breathe, kick, stretch, move, swallow, suck the thumb, and others. While the main stimulation is given specifically for children aged 0-7 years (Siswono, 2004). PAUD teacher's understanding and awareness of the importance and influence of parental education on child development vary. Many do not understand the characteristics of early childhood development, stimulation, and implementation of early detection of early childhood growth and development. Asih Waluyo Jati Clinic is a Pratama clinic that has a program about child development. With community service at the Asih Waluyo Jati Primary Clinic, it is expected that the knowledge and understanding of PAUD teachers on the characteristics of growth and development, simulation, and implementation of early detection of early childhood growth and development can be increased. The activity was carried out at the Pratama Asih Waluyo Jati Clinic on Sunday, October 8, 2017, at 09.00 to 15.00 with material about problems of child growth and development inÂ Indonesia, the importance of monitoring children's growth and development, the participation of teachers and parents in child development, how to detect children's growth and how to detect a child's development. The methods used in this activity include lectures, questions and answers, and role-play. Most of the participants understood what early detection and stimulation of children's growth and development were. But about the types and ways of early detection that must be done many do not understand. The participant's lack of understanding about the types and methods of early detection of children when training has not been conducted is likely because since they have never attended training and there has been no socialization from the education office related to monitoring child development. After being given the material, the participants understood that the types of early detection were detection of growth, development, and mental-emotional. Stimulation is very important as a form of intervention so that the child's growth and development can take place optimally.Keywords: early childhood, stimulation, early detection, growth, development